2019
DOI: 10.4103/jiaps.jiaps_30_18
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on neonatal surgical mortality: A multivariable analysis of predictors of mortality in a resource-limited setting

Abstract: Purpose:The aim of this research is to study the predictors of neonatal surgical mortality (NSM)-defined as in-hospital death or death within 30 days of neonatal surgery.Materials and Methods:All neonates operated over the study period of 18 months were included to evaluate NSM. The evaluated preoperative and intraoperative variables were birth weight, gestation age, age at presentation, associated anomalies, site and duration of surgery, intraoperative blood loss, and temperature after surgery. Assessed posto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
5
18
0
3
Order By: Relevance
“…[22][23][24] Puri et al observed that LBW and premature babies were associated with a higher probability of NSM. [21] The same was observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…[22][23][24] Puri et al observed that LBW and premature babies were associated with a higher probability of NSM. [21] The same was observed in this study.…”
Section: Discussionsupporting
confidence: 88%
“…For achieving the best outcomes, optimization of perioperative stress factors is required apart from a high degree of surgical precision. Factors significantly associated with poor survival outcomes after newborn surgery include preoperative - low birth weight, lesser gestational age, positive blood cultures, and associated congenital anomalies; intraoperative - prolonged duration of surgery, blood loss of >10% blood volume, and intraoperative hypothermia; and postoperative - a requirement of mechanical ventilation for a prolonged duration, need for high-dose of vasopressors, postoperative sepsis, major complications in the postoperative period, and prolonged fasting [ 1 ]. A number of these risk factors are linked to unnecessary intra-hospital or inter-hospital transport of newborns [ 2 , 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The care of a surgical newborn is extremely challenging and requires the continuous involvement of skilled neonatologists for favorable outcomes. Despite a better understanding of postnatal and transitional neonatal care, the mortality rates among surgical newborns can be as high as >60% in developing countries [ 1 ]. Numerous preoperative, intraoperative, and postoperative factors have been linked with poor survival outcomes in these newborns [ 1 , 2 ] One major risk factor is the transport of critically ill and/or preterm surgical newborns to and from the operation room (OR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides that, neonatal surgery requires expert special training to minimize the duration of surgery and well-equipped SICU with trained manpower. 1,19 In our experiences, despite this relatively high mortality rate, it has certainly decreased in recent years as compared to the rate from previous years. This downward trend can likely be attributed to an improvement in surgical techniques, neonatal anesthesia, modern ventilatory support, and advanced intensive care management.…”
Section: Discussionmentioning
confidence: 57%